A neck strengthening protocol in adolescent males and females for athletic injury prevention - Fisher, J. P.; Asanovich, M.; Cornwell, R.; Steele, J. (Journal of Trainology, 2016)
Sport plays a major role in the physical activity, wellbeing and socialisation of children and adults. However, a growing prevalence of concussions in sports persists, furthermore, that subconcussive forces are responsible for neurodegenerative conditions. Current approaches towards concussion prevention are dependent upon coaching strategies and enforcement by referees, or only attempt to reduce further injury, not prevent initial injury occurring. A growing body of research has shown that strengthening the muscles of the neck might serve to reduce head acceleration, change in velocity and dissipate kinetic energy from concussive and subconcussive forces. Design: Following ethical approval and parental consent a single arm, pilot study recruited 13 male and 13 female high school stu dents to undertake 8 weeks of neck strengthening exercises 2 d.wk-1. Method: A low-volume, time-efficient approach considered progressive strength training for neck extension, flexion, and right- and left-lateral flexion exercises for a single set to muscular failure. Results: Strength outcome data was analysed using paired samples t-tests comparing predicted 1-repetition maximum for week 1 and week 8 revealing significant strength improvements for both males and females for all exercises; p < 0.001. Effect sizes were very large (2.3-4.3) for all exercises for both males and females. Conclusions: Participants showed very large increases in neck strength suggesting previous detrained condition and the potential to significantly improve strength using a simple, low volume, resistance training protocol. Athletic training should prioritise health of participants and longevity of career and as such the authors present a neck strengthening protocol with a view to reducing injury risks.